Finding Our Way on the Web: Exploring the Role of Waypoints in Search Interaction - White, Ryen W.; Singla, Adish (20th International World Wide Web Conference (WWW 2011), Pages: 147-148 Hyderabad, India, 2011)
Information needs are rarely satisfied directly on search engine result pages. Searchers usually need to click through to search results (landing pages) and follow search trails beyond those pages to fulfill information needs. We use the term waypoints to describe pages visited by searchers between the trail origin (the landing page) and the trail destination. The role that waypoints play in search interaction is poorly understood yet can be vital in determining search success. In this poster we analyze log data to determine the arrangement and function of waypoints, and study how these are affected by variations in information goals. Our findings have implications for understanding search behavior and for the design of interactive search support based on waypoints.